PdAg/alumina membranes prepared by high power impulse magnetron sputtering for hydrogen separation. (19th April 2018) - Barison, S.; Fasolin, S.; Boldrini, S.; Ferrario, A.; Romano, M.; Montagner, F.; Deambrosis, S.M.; Fabrizio, M.; Armelao, L.
Abstract: The development of hydrogen purification membranes that meet market demands such as high purity, dynamic hydrogen production even at small scale, and reduced costs is still an open question. With this view, the present study aims at developing, for the first time, a method based on high power impulse magnetron sputtering for the deposition of Pd77Ag23 (wt%) films onto porous alumina substrates to achieve composite membranes with high hydrogen permeability and stability. This technique allows the deposition of films also on complex geometries and can be easily scaled up, thus making this technology a potential candidate for preparing high performing membranes. Membranes made by stable and porous alumina supports and metallic, dense and crystalline Pd77 Ag23 layers, from 3.5 μm to 17 μm thick, have been prepared and tested. The membranes showed good hydrogen permeability values, showing flux values up to a maximum of 0.62 molH2 m −2 s −1 at 450 °C and ΔP of 300 kPa. The resistance to hydrogen embrittlement and the chemical inertness to syngas were also demonstrated. Highlights: HiPIMS was used to produce membranes for hydrogen separation. We developed composites membranes based on Pd77Ag23 (wt%) films on porous alumina. Hydrogen fluxes up to 0.62 mol m −2 s −1 at ΔP of 300 kPa and 450 °C were measured. Good resistance to embrittlement and syngas was ascertained.